2014
DOI: 10.1002/chin.201430235
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Secondary Metabolites from the Genus Xylaria and Their Bioactivities

Abstract: Review: 64 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…However, few studies conducted on the active metabolites of Neofusicoccum parvum, and its antioxidant activity accounted for the highest proportion in the current study, which has never been reported in previous studies [99,100]. Besides, Xylaria species are widely distributed on the temperate to the tropical zones in the terrestrial globe, and fungi of this genus have been proved to be potential sources of novel secondary metabolites, and many of them have biological activities related to drug discovery, including cytotoxic, antimalarial, and antimicrobial activities [101]. In terms of bioactivity, active extracts of DS16-1 (Phomopsis sp.…”
Section: Discussionsupporting
confidence: 43%
“…However, few studies conducted on the active metabolites of Neofusicoccum parvum, and its antioxidant activity accounted for the highest proportion in the current study, which has never been reported in previous studies [99,100]. Besides, Xylaria species are widely distributed on the temperate to the tropical zones in the terrestrial globe, and fungi of this genus have been proved to be potential sources of novel secondary metabolites, and many of them have biological activities related to drug discovery, including cytotoxic, antimalarial, and antimicrobial activities [101]. In terms of bioactivity, active extracts of DS16-1 (Phomopsis sp.…”
Section: Discussionsupporting
confidence: 43%
“…However, few studies conducted on the active metabolites of Neofusicoccum parvum, and its antioxidant activity accounted for the highest proportion in the current study, which has never been reported in previous studies [100,101]. Besides, Xylaria species are widely distributed on the temperate to the tropical zones in the terrestrial globe, and fungi of this genus have been proved to be potential sources of novel secondary metabolites, and many of them have biological activities related to drug discovery, including cytotoxic, antimalarial, and antimicrobial activities [102]. μg/mL [103].…”
Section: Bioactivity Evaluation Of Fungal Endophytessupporting
confidence: 43%
“…49 Cytochalasin E was identified as the most active component in brine shrimp toxicity and phytotoxicity potency in the fungal endophyte. The preliminary SAR analysis suggested that cytochalasin E with a characteristic 13-membered macrocyclic vinyl carbonate group could most likely result in strong activity.…”
Section: H− 1 H Cosy and Hmbc Correlations As Shown Inmentioning
confidence: 99%